Rethinking the Third World Novel - Lucero, Adelaida (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Third World fiction emanates from the Third World experience of exploitation, dehumanization and dislocation, shaped by the oppressive triad of geography, culture and history. As the author treats of the agonies, protestations and aspirations of file wretched of the earth, the novel revolves around two main complementary themes: protest and affirmation. The protest, which occurs in three levels, is directed externally or internally, against colonizers and minority power groups, and neocolonizers and sub-oppressors, respectively. The theme of affirmation comes in two forms: the assertion of a glorious past, culture, or civilization, and the affirmation of human dignity, fraternity and liberty. When these themes thus assault lie consciousness of the reading millions, the possibilities for collective social transformation become tremendous.